Determinan Balita Stunting wilayah Kecamatan Kebayoran Lama - Elmi Ornelia Umboh (PROFESSIONAL HEALTH JOURNAL, 2023)
Stunting can occur due to insufficient intake of adequate nutrition, inadequate nutrient intake, as well as other environmental and social factors. This study employed a quantitative approach to identify the correlation between determinant factors and the occurrence of stunting. The instrument used was a questionnaire, and the product-moment correlation analysis was employed as the analytical technique. The results of this study indicate that there is a strong, moderate, and no correlation between determinant factors and the occurrence of stunting, including social aspects, health behavior, environmental health, and overall health.